Greenland Ice Sheet Surface Topography and Drainage Structure Controlled by the Transfer of Basal Variability - Ignéczi, Ádám; Sole, Andrew J.; Livingstone, Stephen J.; Ng, Felix S. L.; Yang, Kang (Frontiers in Earth Science, 2018)
Ice flow can transfer variations in basal topography and basal slipperiness to the ice surface. Recent developments in this theory have made it possible to conduct numerical experiments to predict mesoscale surface topographical undulations and surface relief on an ice sheet-scale. Focussing here on the contemporary Greenland Ice Sheet (GrIS), we demonstrate that the theory can be used to predict the surface relief of the ice sheet from bed topography, ice thickness and basal slip ratio datasets. In certain regions of the GrIS our approach overestimates, while in others underestimates, the observed surface relief. The magnitude and spatial pattern of these mismatches correspond with the theory’s limitations and known uncertainties in the bed topography and basal slip ratio datasets. Our prediction experiment establishes that the first-order control on GrIS surface relief is basal topography modulated by ice thickness, surface slope and basal slip ratio. Additional analyses show that the surface relief, which is controlled by the bed-to-surface transfer of basal topography, preconditions the large scale spatial structure of surface drainage, with other factors such as surface runoff modulating the actual drainage system through influencing the temporal evolution of meltwater features. It follows that the spatial structure of surface drainage depends strongly on the transfer of basal topography to the ice surface. These findings represent an important step towards investigating and understanding the net long-term (>102 years) effect of surface drainage on ice sheet mass balance and dynamics during deglaciation events.